Yrityksille suunnattujen koronatukien vaikutukset Suomessa - Väliraportti: kirjallisuuden tuloksia ja tukien kohdentuminen suomalaisille yrityksille - Olli Ropponen; Heli Koski; Otto Kässi; Nelli Valmari; Ilkka Ylhäinen; Johannes Hirvonen (The Research Institute of the Finnish Economy (ETLA), 2024)
– This study examines the allocation of business subsidies introduced due to the COVID-19 pandemic to different types of companies. The results show that most of the supported companies would not have needed the subsidy, as they would have remained profitable also in the absence of it. Furthermore, companies incurring losses before the pandemic (zombie companies) received COVID-19 subsidies more often than other companies. The subsidies also directed more often to companies with productivity lower than the median productivity. The targeting of subsidies to low-productivity companies slows down future productivity development and economic growth, as labor and capital are more likely to remain in less productive businesses. The study also includes a literature review of the economic literature related to business subsidies during the COVID-19 pandemic.
Keywords: H22; H25; H32; 330; Corporate subsidies; Covid-19 pandemic; Subsidy allocation; Covid-subsidy literature